2013
DOI: 10.1159/000354027
|View full text |Cite
|
Sign up to set email alerts
|

On-Spot Brilliant Cresyl Blue Staining in Fine Needle Aspiration, a Novel Technique for Cytological Diagnosis

Abstract: Objective: Application of on-spot staining with brilliant cresyl blue, a supravital stain, was investigated in fine needle aspirates from breast, lymph node and thyroid. Study Design: Patients with palpable breast lumps, lymph nodes and thyroid nodules were included in the study. Brilliant cresyl blue was used to stain the smears, which were evaluated for smear adequacy as well as cytological diagnosis. Smears were decolorized and subjected to Pap and/or HE staining for comparison. Results: Smears which were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 6 publications
1
4
2
Order By: Relevance
“…In our study, BCB was the least favored of all the smears as the background staining was too bright and smudgy, the cell morphology was not clear, with smudgy staining of the nucleus and cytoplasm. However, the study by Sofi et al showed BCB to give good cytoplasmic and nuclear details which is in contrast to our finding. This may be due to the fact that we have done a comparative evaluation of four rapid stains.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In our study, BCB was the least favored of all the smears as the background staining was too bright and smudgy, the cell morphology was not clear, with smudgy staining of the nucleus and cytoplasm. However, the study by Sofi et al showed BCB to give good cytoplasmic and nuclear details which is in contrast to our finding. This may be due to the fact that we have done a comparative evaluation of four rapid stains.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the study by Sofi et al 9 showed BCB to give good cytoplasmic and nuclear details which is in contrast to our finding. This may be due to the fact that we have done a comparative evaluation of four rapid stains.…”
Section: Whocontrasting
confidence: 99%
See 1 more Smart Citation
“…Results obtained in our study were similar to the study done by Lateef et al 10 They were also used Brilliant cresyl blue for rapid staining. They assess the comparative diagnostic efficacy of brilliant cresyl blue stain with Pap stain.…”
Section: Comparison Of Diagnostic Accuracysupporting
confidence: 91%
“…In this study, the on-site evaluation was done by cytopathologists after staining the smears with toluidine blue. Although there are a few similar studies available that have used Diff-Quick, ultrafast Papanicolaou, and brilliant cresyl blue stains,[ 2 ] one study by Hemalatha et al . [ 3 ] went one step further and tried to evaluate the adequacy on unstained smears.…”
mentioning
confidence: 99%